The clinicopathological features, treatment outcomes and follow-up results of 47 ectopic thyroid gland cases: a single-center retrospective study - Gao, Ming; He, Qi; Li, Liwen; Ji, Feihong; Ding, Yalei; Sun, Qixuan; Qiu, Xinguang (Frontiers in Endocrinology, 2023)
Background: Ectopic thyroid gland (ETG) is an uncommon clinical condition, presenting various challenges and limitations in its regulate diagnosis and treatment currently. This study aims to enhance our understanding of ETG and improve the strategies for its diagnosis and treatment.The retrospective single-center study was conducted, encompassing clinical data from ETG patients screened at our institution between 2013 and 2022. Patients were categorized based on the location of the disease, and follow-ups were performed on each.Results: This study included a total of 47 patients who were confirmed to hav confirmed to have ETG.Among them, we found 29 cases of accessory thyroid and 18 cases of aberrant thyroid. Furthermore, 42 cases exhibited the single ETG, while 5 cases displayed the double ETG. The distribution of the ETG was as follows: 20 were lingual, 10 were submandibular, 10 were lateral cervical, 4 were thoracic mediastinal, 1 was esophageal, and 7 were ovarian. Of these cases, 22 patients underwent surgery, 18 received thyroid hormone replacement therapy, and 7 were placed under observation. All patients were followed up for 59.4 (12-117) months. No significant abnormalities were detected at the conclusion of the follow-up period.ETG is frequently observed in the head and neck, particularly in lingual. Accessory thyroid glands are commonly reported, with most cases being single ETG. Notably, these glands usually do not manifest specific clinical symptoms. Therefore, the appropriate and comprehensive examinations during the initial diagnosis are crucial to avoid misdiagnosis. Treatment should be individualized, and long-term follow-up is essential for managing ETG effectively.